RELIABILITY-CENTERED MAINTENANCE (RCM) EVALUATION IN THE INDUSTRY APPLICATION, CASE STUDY: FERTILIZER COMPANY, INDONESIA - Rahayu Khasanah (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2016)
Nowadays, Reliability-centered Maintenance (RCM) has become the solution to determine the type of maintenance tasks and inspections needs to be performed to the assets in achieving effective and efficient maintenance. However, implementing RCM is not enough to achieve optimization of maintenance planning. The evaluation, as one of the important point should be done to prove the benefits of RCM and to continuously improve the maintenance planning. In this study, the effects of RCM implementation in the industry application were evaluated, as a step for continuous improvement in RCM application. The case study is an Ammonia plant in a fertilizer company in Indonesia. This research evaluates the RCM effects by investigating and analyzing maintenance cost as evaluation parameter. In general, the findings from the investigation of case study affirm that RCM implementation do reduce the maintenance cost. Overall, the study shows that RCM implementation brings many benefits to the company by reducing maintenance cost which can be resulted as the higher profit for the company.Keyword: RCM Evaluation, Maintenance Cost